MIGRATIONSERFARINGEN I DE POLSK-DANSKE FORFATTERES VÆRKER - Schab, Sylwia Izabela (Folia Scandinavica Posnaniensia, 2017)
The aim of the article is to analyze works written by four Polish-Danish authors in terms of defining the poetics they use to communicate their migration experience. The migration experience is to be understood as a never-ending process of translating own identity to a new cultural context. The point of departure for the analysis are selected works of four Polish Danish authors: Alicja Fenigsen, Janina Katz, Bronisław Świderski and Grzegorz Wróblewski. The author of the article discusses also the existence/ non-existence of a specific Polish-Danish migration aesthetic by comparing the analyzed works.